VIHARA DAN PLURALISME PADA MASA JAWA KUNA ABAD VIII - XI MASEHI (TINJAUAN DATA PRASASTI) - Agni Sesaria Mochtar (Berkala Arkeologi, 2015)
The era of reformation in Indonesia was supposedly articulated with the pluralism of the society. Sadly, many cases regarding religious and ethnic conflicts pronounced the opposite, whereas pluralism and religious tolerance were two of the main characters of the nation since the days of the ancestors. The legacy of those two characters is actually able to be observed through cultural heritage, as a messenger from the past. This study examines one aspect of the practice of religious tolerance, which recorded in the ancient inscriptions from 8th to 11th AD., which selected through purposive sampling procedure. The aforementioned aspect was regarding the important role of ancient vihÄra as a symbol of religious tolerance in society. Such role was the impact of its functions, which are different with todayâ€™s modern function. This information on the function and role of the vihÄra in ancient Java is provided to support modern Indonesian society to understand their material cultural heritage.